Parasite - Coates, Darcy (Poisoned Pen Press, 2020)
"When a guard discovers an unusual lifeform on her remote moon outpost, she disregards protocol to investigate, with catastrophic consequences. The parasitic alien wears its victims' skins and adopts their personalities. It's a perfect disguise, and allows the creature to spread without being detected. By the time humanity realizes it's facing extinction, a third of its space stations have already gone dark. As the alien's ruthless progress collapses communication networks, wipes out defenses, and leaves hundreds of stations to fend for themselves, a handful of remarkable individuals must find a way to battle the greatest threat the universe has ever encountered...or die trying"--